Description of immatures of Berosus decolor Knisch, 1924 (Coleoptera: Hydrophilidae: Berosini), with emphasis on chaetotaxy and morphometry - Rodriguez, Georgina; Archangelsky, Miguel; Torres, Patricia L. M. (Zootaxa, 2015)
The preimaginal stages of Berosus decolor Knisch, 1924 are described for the first time, including illustrations of the egg case and all larval instars. Larval morphology of this species is studied emphasizing chaetotaxic and morphometric analyses. The egg case lacks a mast and contains 2‒3 eggs; all larval instars are characterized by the following features: presence of 6 teeth on anterior margin of nasale; left epistomal lobe carrying 14‒16 strong and curved setae (gFR2); seta FR1 elongate, inserted posteriorly to seta PA7; pore FR14 absent; parietale with spinulae in the area between setae PA5 and PA12; mandibles asymmetrical; seta MN1 minute; first antenommere with a digitiform projection on distal inner margin; antennal sensilla AN8 and AN9 absent; maxillary sensilla MX10 hair-like, MX11 and MX16 with an intermediate shape between hair-like and spine-like; labial sensilla LA4 and LA15 absent; seta LA2 present, minute; abdomen with 7 pairs of tracheal gills. The morphology of the egg cases and larvae within the genus Berosus are compared and discussed.